(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper aims to review the latest researches on smoothness-roughness sensation of fabric, which is considered as one of the important factors that affect clothing comfort. To begin with, the definition of clothing comfort and position of smoothness-roughness sensation within clothing comfort were classified. Further the physical and neurophysiological understanding of sensation with research gap was reviewed. Lastly sensation evaluation methods were reviewed for further development of new instruments. This papers aims to be a reference in future for related studies.